Fighting corruption: How binding commitments of business firms can help to activate the self-regulating forces of competitive markets - Ingo Pies; Stefan Hielscher (Martin-Luther-Universität Halle-Wittenberg, Lehrstuhl für Wirtschaftsethik, 2019)
Corruption is a serious and complex challenge for modern societies. Fighting and preventing corruption thus requires constructive learning processes. In this paper, we systematically integrate a market ethics perspective with a business ethics perspective constitutive for the study of 'ordonomics'. In doing so, we argue that, first, companies have a(n) (common) interest in actively fighting corruption using collective forms of self-regulation and, second, we show what companies can do about it internally. We derive the first argument from a market ethics perspective that shows how companies suffer from a race to the bottom that results from corruption under market competition. The second argument is based on a business ethics perspective that shows how cartels of silence within companies can create significant obstacles for well-meaning top management to address the problem effectively. – – Korruption ist eine ernste und komplexe Herausforderung für moderne Gesellschaften. Korruptionsprävention erfordert daher konstruktive Lernprozesse. In diesem Beitrag wird ein ordonomisches Orientierungsangebot entwickelt, das die Wirtschafts- und Unternehmensethik systematisch miteinander in Verbindung bringt. Unser zweigeteiltes Argument lautet wie folgt: Erstens kann aus wirtschaftsethischer Sicht gezeigt werden, dass Korruptionsprävention im Sinne einer kollektiven Selbstregulierung nicht gegen Unternehmen in Stellung gebracht werden muss, sondern in ihrem eigenen Interesse liegend ausgewiesen werden kann. Der Grund hierfür liegt in der Erkenntnis, dass der Korruptionswettbewerb eine kollektive Selbstschädigung für alle beteiligten Unterhemen darstellt. Zweitens kann aus unternehmensethischer Perspektive argumentiert werden, dass Whistle-Blowing Systeme interne Schweigekartelle aufzulösen in der Lage sind, welche ein wichtiges Hindernis für die Etablierung eines wirksamen Integritätsmanagements darstellen.
urn:nbn:de:gbv:3:2-116162
Keywords: 330; corruption; prevention of corruption; governance; commitments; social dilemmas; integrity management; Korruption; Korruptionsprävention; Selbstbindungen; soziale Dilemmata; Integritätsmanagement